Juridical Normative Implications of Constitutional Court Decision 135/PUU XXII 2024 on Elections - Walangitan, Samuel; Lubis, Ilhamsyah; Oktama, Yogi (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the normative legal implications of Constitutional Court Decision Number 135/PUU-XXII/2024 on the legal framework governing general elections and regional head elections in Indonesia, particularly in relation to the regulation of simultaneous elections and broader electoral reform. Research Methodology: This research employs a normative legal research method with a qualitative approach. The analysis is conducted through an examination of statutory regulations, Constitutional Court decisions, and relevant legal doctrines and scholarly literature in the fields of constitutional and election law. Results: The findings indicate that Constitutional Court Decision Number 135/PUU-XXII/2024 has significant implications for the structure of electoral regulation in Indonesia. The decision redefines the legal relationship between general elections and regional head elections by emphasizing their institutional separation to ensure constitutional consistency and strengthen legal certainty within the electoral system. Conclusions: The study concludes that the Constitutional Court reaffirmed its constitutional role as the guardian of the Constitution by providing clear normative direction regarding the design and implementation of elections within the framework of constitutional democracy. Limitations: This study is limited to normative legal analysis and does not incorporate empirical or socio-political data concerning the practical implementation of the decision. Contributions: This research contributes to the development of constitutional and election law scholarship by clarifying the normative legal implications of a recent Constitutional Court decision and offering a conceptual foundation for future electoral reform and electoral law policy formulation in Indonesia.